"Eagle syndrome" An Enigma to Dentists - Prashant Prakash Jaju; Prashant V Suvarna; Nipa J Parikh (Wolters Kluwer Medknow Publications, 2007)
"Eagle syndrome" is caused due to elongated styloid process. Generally it is asymptomatic, but on occasions it can cause severe physical and psychological trauma to the patient. Current article reviews about this innocuous syndrome with detailed insight of the anatomy, embryology, theories involved in its elongation (ossification), clinical and radiological features and its surgical management.